Expression of manganese superoxide dismutase in patients with breast cancer - Shih-Meng Tsai; Ming-Feng Hou; Szu-Hsien Wu; Bao-Wen Hu; Sheau-Fang Yang; Wan-Tzu Chen; Chee-Yin Chai; Hsu Ma; Li-Yu Tsai; 蔡世盟; 侯明鋒; 吳思賢; et al. (Kaohsiung Journal of Medical Sciences, 2011)
Breast cancer has become the second leading cancer among females in Taiwan. Even though the etiology of breast cancer is multifactorial, oxidative stress plays an important role in the carcinogenesis. The purpose of this study was to investigate the expression of manganese superoxide dismutase (MnSOD), one of the major antioxidant enzymes that is involved against oxidative stress, in adjacent cancer-free breast tissues and neoplasm tissues within the same patient. Sixty-five breast cancer patients’ formalin-fixed tissue blocks, including ductal carcinoma in situ (DCIS) tissues, invasive ductal carcinoma (IDC) tissues, and adjacent cancer-free tissues, were evaluated by immunohistochemical stain. Meanwhile, their demographic and clinical information was also collected. The combined scores of MnSOD-positive cell proportion and MnSOD staining intensity were compared for different tissues within the same patient. The results showed that the mean combined scores of MnSOD expression in adjacent cancer-free tissues (6.33), IDC (5.30), and DCIS (3.78) were significantly different when assessed by repeated-measurement analysis of variance (F=14.17, p<0.001). Additionally, the results revealed that the distribution of strong MnSOD protein expression was 80.0%, 72.3%, and 52.3% in adjacent cancer-free tissues, IDC, and DCIS, respectively. However, there was no statistically significant relationship between the expression of MnSOD and grades of breast cancer or other clinicopathologic variables. We suggest that the expression of MnSOD in neoplasm tissues, independent of the clinicopathologic characters, plays a critical role in breast cancer biology.